Deletional tolerance prevents AQP4‐directed autoimmunity in mice. Issue 3 (25th January 2017) - Vogel, Anna‐Lena; Knier, Benjamin; Lammens, Katja; Kalluri, Sudhakar Reddy; Kuhlmann, Tanja; Bennett, Jeffrey L.; Korn, Thomas
Abstract : MHC class II (IA b )‐restricted T‐cell responses against AQP4(201–220) are only elicited in Aqp4 −/− mice while WT mice lack T cells against this immunogenic epitope due to thymic deletional tolerance. Reconstitution of Rag1 −/− mice with the mature T‐cell repertoire of Aqp4 −/− mice and subsequent immunization with AQP4(201–220) results in an encephalomyelitic syndrome. However, histologic lesions reminiscent of human neuromyelitis optica are only induced upon additional transfer of anti‐AQP4 antibodies. Abstract : Neuromyelitis optica (NMO) is an autoimmune disorder of the central nervous system (CNS) mediated by antibodies to the water channel protein AQP4 expressed in astrocytes. The contribution of AQP4‐specific T cells to the class switch recombination of pathogenic AQP4‐specific antibodies and the inflammation of the blood–brain barrier is incompletely understood, as immunogenic naturally processed T‐cell epitopes of AQP4 are unknown. By immunizing Aqp4 −/− mice with full‐length murine AQP4 protein followed by recall with overlapping peptides, we here identify AQP4(201‐220) as the major immunogenic IA b ‐restricted epitope of AQP4. We show that WT mice do not harbor AQP4(201–220)‐specific T‐cell clones in their natural repertoire due to deletional tolerance. However, immunization with AQP4(201–220) of Rag1 −/− mice reconstituted with the mature T‐cell repertoire of Aqp4 −/− mice elicits an encephalomyelitic syndrome. Similarly to the T‐cell repertoire, the B‐cell repertoire of WT mice is "purged" of AQP4‐specific B cells, and robust serum responses to AQP4 are only mounted in Aqp4 −/− mice. While AQP4(201–220)‐specific T cells alone induce encephalomyelitis, NMO‐specific lesional patterns in the CNS and the retina only occur in the additional presence of anti‐AQP4 antibodies. Thus, failure of deletional T‐cell and B‐cell tolerance against AQP4 is a prerequisite for clinically manifest NMO.